Biologia do conhecer (BC) e biologia do amar (BA): transgressões epistêmico-teórico-metodológicas e os movimentos autotransformativos discentes-docentes - Visentini, Lucas (2020)
This research deals with the epistemic-theoretical-methodological perspective proposed by the Biology of Knowing and the Biology of Loving, by Humberto Maturana et al. With the accomplishment of the study we aimed to investigate the contributions of the understandings of epistemic-theoretical-methodological nature presented by the Biology of Knowing and by the Biology of Loving, by Maturana et al., to the Educational Sciences. Furthermore, we intended to investigate the implications of an epistemic-theoretical-methodological nature of the concepts of the Biology of Knowing and the Biology of Loving for the achievement of the autotransformative students-teachers movements; to know the key categories concerning the Biology of Knowing and the Biology of Loving that can enable personal-professional development student-teacher in the flow of our daily living-coexistence and, also, analyzing, from the assumptions of the Biology of Knowing and Biology of Loving, as the love emotion - the affectivity, the lovingness - can be significant in relation to the teaching-learning processes. The study is of a qualitative nature (JOSSO, 2004; 2010) and was woven into five different investigative movements. As an element of the sources used for the construction of knowledge, we highlight bibliographic research (SEVERINO, 2016) and as a tool for data analysis, Discursive Text Analysis was used (MORAES, 2003). Regarding the epistemic-theoretical perspective, we present some categories and their respective authors: Biology of Knowing and Biology of Loving (MATURANA, 1998; 1999; 2000; 2001; 2004), (MATURANA; DÁVILA, 2015); cultural biology (MATURANA; DÁVILA, 2015), (MATURANA; VARELA, 2010); human formation (MATURANA; REZEPKA, 2000), (JOSSO, 2004; 2010); teaching (ARROYO, 2011), (BARCELOS, 2013; 2015; 2016); neuroscience, learning and education (COSENZA; GUERRA, 2011), (SHONKOFF; PHILLIPS, 2000); self-transformation (VISENTINI, 2014; 2019; 2020). Based on the knowledge built and the reflections carried out up to the present moment, the propositions of the Biology of Knowing and Biology of Loving, by Maturana et al., present themselves as true ruptures, epistemic-theoretical-methodological transgressions, with consequences for the achievement of autotransformative student-teacher movements.